Analisis Pengaruh Fitur-Fitur Pada Layanan BRIMobile Terhadap Kepuasan Nasabah ( Studi Pada Pengguna Brimo Di Daerah Istimewa Yogyakarta) Analysis Of The Influence Of BRIMobile Service Features On Customer Satisfaction (Study On Brimo Users In The Specia - Rini Rosfika Uopmabin; Muhammad Supriyadi (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
This study aims to identify and analyze the features of the BRI Mobile service on customer satisfaction with BRImo users in the Special Region of Yogyakarta and this research can increase knowledge about the use of BRImo services.The type of research used is quantitative research, for collecting data by distributing questionnaires. The number of samples in this study were 100 respondents or samples taken from the people of the Special Region of Yogyakarta who used BRImo. Data analysis methodused in this research is multiple linear regression, t test, F test and the coefficient of determination.The results of this study indicate that partially the features of information services, transaction services and communication services have a significant influence on customer satisfaction and simultaneously information services, transaction services and communication services have a significant influence on customer satisfaction.